In situ evolution of surface and bulk properties of Ni/La-doped CeO2 catalysts for CO2 reduction with hydrogen - Belén Bachiller-Baeza; João Elias F.S. Rodrigues; Maricarmen Capel-Sanchez; Javier Gainza; Victoria E. García-Sánchez; Ignacio J. Villar-García; Virginia Perez-Dieste; Carlo Marini; M. Teresa Fernández-Diaz; José A. Alonso; Consuelo Álvarez-Galván (Journal of CO2 Utilization)
In this work, key factors that affect catalytic activity of Ni/La-doped ceria catalysts for the reverse water gas shift reaction (RWGS) have been revealed by applying in situ advanced synchrotron techniques, such as X-ray Absorption Spectroscopy (XAS) and Near-ambient pressure X-ray Photoelectron spectroscopy (NAP-XPS). Complementary ex situ characterization techniques have been also used, adding valuable insights on different physicochemical properties of the catalysts. Lanthanum incorporates into the ceria lattice, increasing oxygen mobility, which has a role in the formation of H2O during the reaction. The optimum substitution degree of Ce by La that maximizes CO yield is close to 10 %. It is found that both bulk and surface Ce3+ proportions depend on the proportion of La, increasing with La content. At a reaction temperature of 873 K, bulk Ce3+ proportions are higher than surface ones. These differences are due to oxidative phenomena, associated to the reactive mixture that take place on the surface, such as CO2 adsorption and H2O formation. Concerning Ni phase, NiO bulk reduction to metallic Ni is very fast (in the range 573–623 K), however, Ni0 and Ni2+ species coexist on the surface during the reaction. It is found that a higher proportion of surface metallic Ni promotes the selectivity towards the RWGS, inhibiting the competing methanation reaction. On the other hand, La doping is relevant for the formation of lanthanum oxycarbonate, which has a role gasifying carbon deposits.